Keanekaragaman Burung Raja Udang di Kawasan Daerah Aliran Sungai (DAS) Marisa, Kabupaten Pohuwato - Harunja, Wahyuni Ws.; Solang, Margaretha; Zakaria, Zuliyanto; Ibrahim, Mustamin; Lamangantjo, Chairunnisah J; Azhar, Rosyid (Jambura Edu Biosfer Journal, 2025)
This study aims to determine the diversity and abundance of kingfisher species in the Marisa watershed, Karangetang Village. The method employed was Point Count, which involved 5 counting points, each 200 meters apart, with a viewing distance of 50 meters and observation time of 20 minutes. The study identified 4 kingfisher species from the Alcedinidae family, two of which are endemic (Ceyx fallax, Pelargopsis melanorhyncha) and two non-endemic (Alcedo meninting, Todirhamphus chloris) in the forest edge area point count 1,2 with diversity index H' = 3,00 (high) and point count  3, 4 and 5 community farmland area with diversity index H' = 3,26 (high). Among the four species, the most dominant was C. fallax (Di = 38,77%), T. chloris (Di = 36,73%), Alcedo meninting (Di = 22,45%), and Pelargopsis melanorhyncha (Di = 2,04%), indicating a moderate dominance in abundance.